Promoting and Hampering Factors in the management of entrepreneurial human capital in the field of health care - SHima KHosravi; Malikeh Beheshtifar; Amin Nikpoor (Tehran University of Medical Sciences, 2022)
Introduction: change and innovation for gaining competitive advantage in health system will lead to the continuation of activities in health care. Therefore, managers ' entrepreneurial orientation to promote organizational goals in the turbulent health industry is one of the requirements of human capital managers. Materials and Methods: In this study , semi-structured interviews were conducted to identify promoting and obstacles in the organizational entrepreneurship factor to design entrepreneurial human resource management model and were analyzed by content analysis method . The population of the study consisted of operational and middle managers in the field of health, among which 20 were selected by non-probability and snowball sampling methods . Results: The results showed that organizations in health care areas are influenced by three factors of managers , employees and environment of the organization and have an impact on the organizational entrepreneurship variable in human capital management. In the case of obstacles and promoting factors, employees and managers had the highest number of codes (meaning unit) respectively. Conclusion : Human capital managers in the field of health by creating the necessary ground in strengthening the driving factors and overcoming the confounding factors of corporate entrepreneurship in their management strategies and processes promote the performance of the staff and personnel  and consequently play a significant role in the health of the entire society .